Metal(loid)-Contaminated Soils as a Source of Culturable Heterotrophic Aerobic Bacteria for Remediation Applications. Issue 9 (21st October 2017) - Pires, Carlos; Franco, Albina R.; Pereira, Sofia I. A.; Henriques, Isabel; Correia, António; Magan, Naresh; Castro, Paula M. L.
ABSTRACT: Heavy metal–contaminated soils are a serious environmental problem. Herein, the culturable heterotrophic bacterial community present on two metal(loid)-contaminated sites in the Northern Portugal was investigated. The bacterial counts ranged from 5.96 to 7.69 and 7.04 to 7.51 (log CFU g −1 soil) in Sites 1 and 3, respectively. The bacterial population was predominantly composed of Firmicutes, Proteobacteria, and Actinobacteria on both sites. The most represented genera in Site 1 were Bacillus (41%) and Pseudomonas (27%), whereas Arthrobacter (21%) and Pseudomonas (13%) were the most represented genera in Site 3. Several bacterial isolates showed tolerance to high concentrations of metal(loid)s, suggesting that both contaminated sites are a valuable source of metal(loid)-tolerant bacteria, which may be further used in bioremediation and/or phytoremediation processes.